The sister queens - Scott, Justin (Severn House, 2024)
"Two rival queens. History's greatest playwright. And a deadly plot for the crown. London, 1600. With no legitimate heir to Queen Elizabeth's throne, and no clear successor with her modern vision of a civilization that thrives in peace and diversity, England is in a supremely perilous moment. Elizabeth's foes understand the power of a poet's voice to shape popular opinion, and force esteemed playwright William Shakespeare to write a script detailing the history of Queen Elizabeth and the Catholic Mary Queen of Scots that will tumble the nation into civil war. Faced with a terrible dilemma, Will must navigate a dangerous path through the corridors of the wealthy, the refuse-filled warrens of London and the byzantine world of Elizabethan politics as he tries to save both his family and his own legacy."--provided by publisher.